An industry update: the latest developments in therapeutic delivery. (January 2018) - Simpson, Iain
This industry update covers the period from 1 September through 30 September 2017, and is based on information sourced from company press releases, scientific literature, patents and various news websites. The month saw the US FDA approve three new molecular entities, Aliqopa (copanlisib dihydrochloride) (Bayer Healthcare); Solosec (secnidazole) (Symbiomix Therapeutics) and Verzenio (abemaciclib) (Eli Lilly and Co). Intarcia Therapeutics Inc. has its application for approval of a novel drug device combination of exenatide for the treatment of diabetes rejected by FDA but said that it will work to address the concerns and refile the application. The impact of biosimilars in the market is steadily increasing with seven biosimilars approved in the USA and Sandoz hoping to add to this with its announcement that FDA has accepted its Biologics License Application for a biosimilar version of Roche's Rituxan. Circassia announced positive top line results of a respiratory drug, Duaklir (for the treatment of chronic obstructive pulmonary disease) and Sarepta (for its new treatment for Duchenne muscular dystrophy). Axovant Sciences Ltd announced the failure if its drug Intepirdine in the treatment of Alzheimer's, adding to a growing list of drug failures in this area. There were a number of developments in the area of oncology with Bristol-Myers Squibb and Infinity Pharmaceuticals announcing an expansion of their collaboration looking at combination treatments, as well as Eli Lilly and Co's approval for Verzenio. Rani Therapeutics and Intra-Cellular Therapies announced successful funding rounds to support their drug programs. Allergan announced a novel licensing deal for its dry eye drug, Restasis, which it hopes would allow it to stave off patent challenges from several companies looking to develop generic versions of the drug. New research suggests that loss of sense of smell can be linked to an increased risk of developing Parkinson's disease.